Development of Android-Based Learning Media Materials for Construction of Flat Side Room Class VIII Junior High School 1 Plandaan Jombang - Khusnul Khotimah; Fitri Umardiyah; Dhuria Ulfa Oktavyanti (APPLICATION: Applied science in Learning Research, 2022)
This study aims to produce android based learning on the material of a flat sidewalk that is feasible to use and as a learning media based on matter expert, media expert, and the opinion of the students. This research is addapted from ADDIE development model, which is the type of research and Development (R&D. There are five stages include: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. Data writing techniques in the form of questionnaire research. Material experts and media experts carry out validation. The developed media was tested on 14 students. The result showed the level of feasibility of the learning media based on: 1) Expert acquisition material total score 3,8 in the category “Valid”. 2) Media Experts obtained a total score of 4,4 in the “Very Valid” category. 3) Student Response to this media at the time of testing was distributed on average shows positive with a total score 4,15 in the category “Very Practical”. Thus the Android Based learning media is used as a learning medium for students of class VIII SMPN 1 Plandaan Jombang.